Studi Performansi Pada Peta Kendali Variabel Dengan Pendekatan Rantai Markov - Mastiadi Tamjidillah (INFO-TEKNIK, 2005)
Many products which are non-conforming with specification from company decision require the development and improvement of control chart to investigation and problematic analyzing. One of tool that used to get information of improvement action is control chart variable with Markov Chain analysis to increase of performance plywood product quality.To acquire information about variable of control chart with Markov Chain analysis can be watched on ARL value, data plotted pattern and calculating of loss function because of scatter pattern, and alternative for selling with discount price in domestic market. All the indicator or output above must be compared by indicator or output control chart  Shewhart. From analysis of variable of control chart performance before the improvement action resulted value ARL is 7,4 % and 1,60 %. Then decrease of loss function Rp. 32.000,- and Rp 16.000,- and after the improvement action resulted value ARL is 5,74 % and 1,55 %, and decreasing of loss function is zero. Pattern plots the data can you said in-control. In the relation with selling alternative using by discount price that explained with finance standard, so that benefit can be excepted than scrapped the alternative are selected.